Green Food Packaging Industry to Explore and Analyze - Wang, Peng; Peng, Huaifang (International Journal of Natural Resources and Environmental Studies, 2024)
In the context of the current increasingly poor global environment and the rising awareness of environmental protection, green food packaging, as an important part of reducing environmental pollution and promoting sustainable development, has attracted widespread attention. Through the SWOT analysis method, this paper analyzes the current development status and trends of the green food packaging industry, and discusses its role in protecting the environment and saving resource consumption. Special attention is paid to the application and development of biodegradable materials, recyclable materials and recycling technologies in green food packaging. In addition, this paper evaluates the impact of policies and regulations on the green food packaging market, and puts forward suggestions and strategies to promote the sustainable development of the industry. In summary, green food packaging is not only an important means to achieve the goal of sustainable development, but also provides far-reaching insights into the future direction of the food packaging industry.